WT1 – Gene expression driven pre-emptive treatment with decitabine for molecular relapse of acute myeloid leukemia after allogeneic stem cell transplant. (September 2021) - Sperotto, Alessandra; Gottardi, Michele; Candoni, Anna; Toffoletti, Eleonora; De Marchi, Roberta; Petruzzellis, Giuseppe; Pizzano, Umberto; Fanin, Renato
Highlights: Relapse of acute myeloid leukemia after allogeneic stem cell transplant represents the most common reason for treatment failure. Prognosis of relapsed patients after transplant is dismal (<15 %). No standard approach is defined for AML relapsed after transplant. Available data indicate that hypomethylating agents and also donor lymphocyte infusons results in higher response and survival rates if employed for molecular relapse.